Alqueva-Pedrógão joint early warning system - Oliveira Costa, C. (2009)
SUMMARY Alqueva multipurpose project, located in the Alentejo region (southern Portugal), is an important project, which main objectives are: the creation of a strategic water reserve in a region with a trend to desertification; the water supply to the population and to irrigation; and the production of electricity. For the project development two main structures were erected: Alqueva and Pedrógão dams. Beyond of its benefits these two dams are also a potential risk for the downstream valley: the probability of failures occurrence in their water retaining capabilities is very low but still possible. In contemporary society potential dam failures as well as the public pressure for a safer environment make mandatory the development of risk mitigation instruments as emergency plans and early warning systems. The paper presents the main characteristics of Alqueva and Pedrógão dams and a risk analysis for the dam-break flood prone area downstream. Finally, it focuses on the technical details of the early warning solution developed to improve the people safety in the nearest zones of the downstream valley.